Isochavicinic Acid and Steroids from Gomphrena globosa L. (Dhaka University Journal of Pharmaceutical Sciences, 2012)
Not available DOI: http://dx.doi.org/10.3329/dujps.v11i1.12493 Dhaka Univ. J. Pharm. Sci. 11(1): 79-81, 2012 (June)